Disposition of Proteins and Lipids in Synaptic Membrane Compartments Is Altered in Q175/Q7 Huntington’s Disease Mouse Striatum - Iuliano, Maria; Seeley, Connor; Sapp, Ellen; Jones, Erin L.; Martin, Callie; Li, Xueyi; DiFiglia, Marian; Kegel-Gleason, Kimberly B. (Frontiers in Synaptic Neuroscience, 2021)
Dysfunction at synapses is thought to be an early change contributing to both cognitive, psychiatric and motor disturbances in Huntington’s disease (HD). In neurons, mutant Huntingtin collects in aggregates, and distributes to the same sites as wild-type Huntingtin including on membranes and in synapses. In this study, we investigated the biochemical integrity of synapses in HD mouse striatum. We performed subcellular fractionation of striatal tissue from 2 and 6-month old knock-in Q175/Q7 HD and Q7/Q7 mice. Compared to striata of Q7/Q7 mice, proteins including GLUT3, NaK ATPase, NMDAR 2b, PSD95, and VGLUT1 had altered distribution in Q175/Q7 HD striata of 6-month old mice but not 2-month old mice. These proteins are found on plasma membranes and pre- and postsynaptic membranes supporting hypotheses that functional changes at synapses contribute to cognitive and behavioral symptoms of HD. Lipidomics analysis of mouse fractions indicated that compared to those of wild-type, fractions 1 and/or 2 of 6 months Q175/Q7 HD had altered levels of two species of PIP2, a phospholipid involved in synaptic signaling, and increased levels of cholesterol ester and decreased cardiolipin species. At 2 months, increased levels of species of acyl carnitine, phosphatidic acid and sphingomyelin levels were measured. EM analysis showed that the contents of fractions 1 and 2 of Q7/Q7 and Q175/Q7 HD striata had a mix of isolated synaptic vesicles, vesicle filled axon terminals singly or in clusters, and ER and endosome-like membranes. However, those of Q175/Q7 striata contained significantly fewer and larger clumps of particles compared to those of Q7/Q7. Human HD postmortem putamen showed differences from control putamen in subcellular distribution of two proteins (Calnexin and GLUT3). Our biochemical, lipidomic and EM analysis show that the presence of the HD mutation conferred age dependent disruption of localization of synaptic proteins and lipids important for synaptic function. Our data demonstrate concrete biochemical changes suggesting altered integrity of synaptic compartments in HD mice that may mirror changes in HD patients and presage cognitive and psychiatric changes that occur in premanifest HD.